Analisis Kesalahan Ejaan dalam Penggunaan Bahasa Indonesia pada Platform Media Sosial : Studi Kasus Menfess Twitter Mahasiswa UPN Veteran Jawa Timur - Ika Arilia Sagita; Shafyrani Aditia; Afiyah Afiyah; Arninda Nur Aini; Taswirul Afkar (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze spelling errors in the use of Indonesian on social media platforms, focusing on a case study of Twitter menfess (X) of Veteran National Development University students in East Java. Social media has become a popular means of communication among students, but the use of Indonesian often uses non-standard language and the use of incorrect spelling. The method used in this study is qualitative descriptive analysis, in which 20 data were collected from menfess posted by students on Twitter (X) during a certain period. The results of the analysis show that there are many spelling errors in the college students' menfess posts on Twitter (X). The findings show that, although university students have an understanding of Indonesian language, the influence of social media and fast communication habits can cause a decline in language quality. This research is expected to provide insights for the development of language policy among university students, as well as raising awareness of the importance of good and correct language use in the digital era.